The Incidence of Atlanto-Occipitalization and Additional Foramina Present in The Dry Skulls of Nepalese Population - Shakya, Rubina; Ranjit, Nirju; Shrestha, Shamsher (Birat Journal of Health Sciences, 2021)
Introduction: Atlanto-occipitalization(AOZ) is one of the congenital anomalies related to craniovertebral synostosis. The clear understanding of its anatomical features and cranial foraminal variants plays a critical role in finding the possible coping mechanism with its pathogenesis such as segmental instability or neurologic deficits.Objective: This study aimed to investigate the incidence of occipitalization of Atlas and related variant foramina, as the baseline awareness of these conditions among the Nepalese population is yet to be documented.Methodology: A retrospective study was performed for the total 86 dry skulls available in the department of Anatomy in Katmandu University of Medical Sciences, Institute of Medical Science, and B.P. Koirala Institute of Health Sciences. The skulls were examined thoroughly to evidence the occurrence of cranio-vertebral variations.Result: Out of 86 human adult skulls, 2 cases (2.32 %) were found with partial AOZ presenting posterior spina bifida close to the midline. Sphenoidal emissary foramen (SEF) was also observed in 17 skulls (19.76 %), an additional foramen lying anteromedial to the foramen ovale. Moreover, one of the skulls (1.16 %) was found with the presence of pterygospinous bar creating an additional foramen ‘foramen of Civinini’ in the lateral pterygoid plate of the sphenoid bone.Conclusion: The incidence of AOZ and pterygospinous bar seems to be quite low as compared to the cases of SEF. However, the knowledge of such variations and the presence of additional foramina carry great significance for orthopedists and neurosurgeons to have prognostic implications and an accurate surgical approach.